Must the surgeon take the pill? Negligence duty in the context of cognitive enhancement - Goold, I; Maslen, H (Wiley, 2014)
Recently, attention has turned to the possibility of enhancing human cognitive abilities via pharmacological interventions. Known as ‘cognitive enhancers’, these drugs can alter human mental capacities, and in some cases can effect significant improvements. One prime example is modafinil, a drug used to treat narcolepsy, which can help combat decreases in wakefulness and cognitive capacity that arise due to fatigue in otherwise healthy individuals. In this paper, we respond to calls in the philosophical and ethical literature that surgeons and other medical professionals should be morally obliged to take cognitively enhancing drugs. We examine whether surgeons who make fatigue‐related errors during patient care might be considered legally obliged to enhance themselves. We focus on liability for a failure to medicate, and conclude that it is highly unlikely that surgeons will be legally obliged to address their fatigue through the use of cognitive enhancing drugs.